Diversity and rabbinization: Jewish texts and societies between 400 and 1000 CE - McDowell, Gavin; Naiweld, Ron; Stökl Ben Ezra, Daniel (Cambridge Semitic Languages and Cultures Ser., 2021)
This volume is dedicated to the cultural and religious diversity in Jewish communities from Late Antiquity to the Early Middle Age and the growing influence of the rabbis within these communities during the same period. Drawing on available textual and material evidence, the fourteen essays presented here, written by leading experts in their fields, span a significant chronological and geographical range and cover material that has not yet received sufficient attention in scholarship.